2015
DOI: 10.3917/mana.181.0078
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Distance and Brazilian Outward Foreign Direct Investment

Abstract: Different studies have discussed the factors that influence outward foreign direct investment (OFDI) from developing countries. However, the choice of location and the role of institutional distance are still controversial. The aim of the present paper is to address the determinants of OFDI from Brazil from the perspective of the host countries. Using a panel data model, we have tested the impact of cultural and institutional distances on OFDI, and noted the moderating effects of the economic performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Most of them highlighted that improvement in institutional quality is positively correlated with more inward FDI and that good governance and better institutional quality lowers the volatility of FDI flows [18][19][20]22,[39][40][41]. The empirical research has also begun to take into account the effects of institutional distance [19,23,[41][42][43][44][45] and natural resources [16,23,26,41,46] as major drivers of FDI. For instance, Busse and Hefeker's [20] study on the relationships between FDI, institutions, and political risk for 83 developing countries from 1984 to 2003 discovered that a number of political risk's sub-components, such as democratic accountability, internal and external conflict, law and order, bureaucracy quality, government stability, and corruption, have a substantial power on FDI inwards.…”
Section: Fdi Quality Of Institutions and Natural Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them highlighted that improvement in institutional quality is positively correlated with more inward FDI and that good governance and better institutional quality lowers the volatility of FDI flows [18][19][20]22,[39][40][41]. The empirical research has also begun to take into account the effects of institutional distance [19,23,[41][42][43][44][45] and natural resources [16,23,26,41,46] as major drivers of FDI. For instance, Busse and Hefeker's [20] study on the relationships between FDI, institutions, and political risk for 83 developing countries from 1984 to 2003 discovered that a number of political risk's sub-components, such as democratic accountability, internal and external conflict, law and order, bureaucracy quality, government stability, and corruption, have a substantial power on FDI inwards.…”
Section: Fdi Quality Of Institutions and Natural Resourcesmentioning
confidence: 99%
“…Qi and Zou [42] pointed out that there will be more FDI outflows when the host and home countries are more distant from one another in terms of economic and legal institutional distance. Tomio and Amal [43] investigated the factors that influence Brazil's outward FDI and demonstrated that institutional distance has a significant positive effect on outward FDI. However, they argued that this effect is constrained by the host country's size and the scale of its bilateral trade.…”
Section: Fdi Quality Of Institutions and Natural Resourcesmentioning
confidence: 99%
“…Brazil and India are two such countries where recent policy changes and economic growth have generated surplus wealth and the recognition of business and educational opportunities abroad. In fact, since pursuing economic reform in the latter half of the 1990s, Brazil and India have become two of the leading sources of outward FDI among developing nations (Athukorala, 2009;Tomio & Amal, 2015).…”
Section: Research Contextmentioning
confidence: 99%
“…As a consequence of the growing prominence of OFDI executed by EMNEs, a plethora of scholarly literature has examined home countries and their respective influence on domestic enterprises OFDI decisions and undertakings [48][49][50][51]. A number of studies have also investigated the nature and determinants of FDI originating from emerging market economies [27,52,53], while other studies have concentrated on the role of institutions in OFDI [54][55][56][57][58].…”
Section: The Empirical Experience Of China Brazil and South Africamentioning
confidence: 99%